A low literacy targeted talking book about radiation therapy for cancer: development and acceptability - Smith, S.; Cabrera-Aguas, M.; Shaw, J.; Shepherd, H.; Naehrig, D.; Meiser, B.; Jackson, M.; Saade, G.; Bucci, J.; Halkett, Georgia; Turner, R.; Milross, C.; et al. (Springer, 2018)
© 2018, Springer-Verlag GmbH Germany, part of Springer Nature. Purpose: To develop a low literacy talking book (written book with accompanying audio-recording) about radiation therapy and explore its acceptability with patients and caregivers. Method: The talking book was developed iteratively using low literacy design principles and a multidisciplinary committee comprising consumers and experts in radiation oncology, nursing, behavioural sciences, and linguistics. It contained illustrations, photos, and information on: treatment planning, daily treatment, side effects, psychosocial health, and a glossary of medical terms. Semi-structured interviews were conducted with patients who self-reported low functional health literacy and caregivers to explore their views on the resource. Thematic analysis using a framework approach informed the analysis. Results: Participants were very satisfied with the content, illustrations, and language in the resource. Most were unfamiliar with the term ‘talking book’, but liked the option of different media (text and audio). The resource was seen as facilitating communication with the cancer care team by prompting question-asking and equipping patients and their families with knowledge to communicate confidently. Conclusions: The low literacy talking book was well accepted by patients and their caregivers. The next step is to examine the effect of the resource on patients’ knowledge, anxiety, concerns, and communication with the cancer care team.